Kamisama kiss. Vol. 18 - Suzuki, Julietta (Shojo beat manga., 2015)
Nanami Momozono is alone and homeless after her dad skips town to evade his gambling debts and the debt collectors kick her out of her apartment. So when a man she's just saved from a dog offers her his home, she jumps at the opportunity. But it turns out that his place is a shrine, and Nanami has unwittingly taken over his job as a local deity! Nanami's journey to the past was a success! She found a way to break the curse and save Tomoe, and he even admitted that he has feelings for her. Now they're both ready to enjoy life as a happy couple. Tomoe is hoping to spend some special alone time with Nanami, but instead they go on a school trip to Okinawa with the entire grade-and things go from tropical paradise to yokai nightmare in no time!